Meningkatkan Kualitas Ikan Gurami (Osphronemus Gouramy) di Desa Panjerejo Melalui Program Pemberian Vitamin dan Pakan Yang Lebih Berkualitas - Sari, Ririn Wahyu Eka; Muslim, Iwan Nur; Cahyani, Dita; Pangkatana, Megi Inge; Rafi, Ariq Muhammad; Khusnah, Yulis Nur; Cahyo, Miftakhul Amin Dwi; Samudro, Bhimo Rizky (Edumedia Solution, 2024)
Panjerejo Village is one of the gourami-producing villages in East Java. This village is located in Rejotangan District, Tulungagung Regency. Gurami fish is one of the freshwater fish commodities that is widely cultivated in Panjerejo Village. Even though it is widely cultivated, fish farmers are also faced with various challenges that affect the growth of their fish. These challenges are grouped into two factors, namely internal factors and external factors. Therefore, KKN UNS Group 03 seeks to increase the technical knowledge and skills of fish farmers through a socialization program for the development of gourami fish cultivation with a focus on providing vitamins and quality feed. This program involves the stages of problem identification, data collection, program planning, and program implementation. Through this activity, it is hoped that it can increase the knowledge and technical skills of gourami fish farmers and make a positive contribution to the local economy of Panjerejo Village. The results show an increased understanding of the importance of providing nutrition and good maintenance techniques for gourami fish farmers.